Head impact kinematics and brain deformation in paired opposing youth football players - Milef, G. M.; Miller, L. E.; DiGuglielmo, D. M.; Payne, T. D.; Filben, T. M.; Urban, J. E.; Stitzel, J. D. (Journal of Applied Biomechanics, 2022)
Approximately 3.5 million youth athletes play tackle football in the United States alone.1 Football has gained attention for its relatively high rate of concussion injuries compared to other sports. Specifically, concussions account for 9.6% of all youth football injuries.2 Concussions are a serious injury, but the majority of head impacts experienced by football players are subconcussive. Although these impacts do not result in acute signs and symptoms of concussion, evidence suggests that accumulated repetitive subconcussive impacts may be associated with long-term neurological damage and can cause changes in the brain after a single season.3,4 As adolescence is a time of brain growth and development, understanding head impact exposure (HIE) is of utmost importance to mitigate adverse effects of head impacts in youth football.